2020
DOI: 10.1080/00220671.2020.1759495
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals and classroom goal structures: Do they need to match?

Abstract: It is often assumed that students' personal achievement goals are most beneficial when they match the goal structures of the classroom, but interaction between achievement goals and goal structures is not well researched. In this study, we aim at providing a nuanced picture of the direct, interaction, and nonlinear effects of achievement goals and goal structures on test performance and autonomous motivation. We used multiple linear regressions, including interaction and quadratic terms, in combination with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
4
1
Order By: Relevance
“…The results of this study are different from previous studies, which found that GO mastery was a predictor of metacognitive skills, while performance-approach and performance-avoidance had no direct or indirect influence on SR metacognitive (Al-Harthy et al, 2010;Fadlelmula et al, 2015). Several studies have proven that each type of GO has a different effect on learning strategies and achievement through dynamic interactions with various other variables (such as the level of task difficulty, class goal structure) (Hofverberg & Winberg, 2020;Mouratidis et al, 2018). In the context of PJJ, the GO performance approach was a positive predictor of academic achievement, while GO mastery was not a predictor, and GO performance-avoidance was a negative predictor of academic achievement (Neroni et al, 2018).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The results of this study are different from previous studies, which found that GO mastery was a predictor of metacognitive skills, while performance-approach and performance-avoidance had no direct or indirect influence on SR metacognitive (Al-Harthy et al, 2010;Fadlelmula et al, 2015). Several studies have proven that each type of GO has a different effect on learning strategies and achievement through dynamic interactions with various other variables (such as the level of task difficulty, class goal structure) (Hofverberg & Winberg, 2020;Mouratidis et al, 2018). In the context of PJJ, the GO performance approach was a positive predictor of academic achievement, while GO mastery was not a predictor, and GO performance-avoidance was a negative predictor of academic achievement (Neroni et al, 2018).…”
Section: Discussioncontrasting
confidence: 96%
“…Self-confidence and GO are motivational variables that play an essential role in SRL and academic achievement (Honicke et al, 2020). Various studies have found that individuals will adopt GO according to their perception of GO in the learning environment (Boden et al, 2020;Fadlelmula et al, 2015;Hofverberg & Winberg, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Performance goals were unimportant in comparison to other variables for predicting Students' achievement, with very low VIPs in all subjects and an average VIP not significantly above zero. This lack of association between performance goals and achievement is in line with the results of a recent study by Hofverberg and Winberg (2020a), based on another large sample and using a different measure of achievement. In the present study, the performance goal construct included items pertaining to both performance approach and avoidance goals.…”
Section: Importance Of Motivational Characteristics For Student Achiesupporting
confidence: 89%
“…It might be tempting to speculate that the Swedish classroom goal structures (Ames, 1992) in general may have emphasized mastery goals before performance goals and, according to the interaction effect model by Murayama and Elliot (2009), thereby rendered performance goals less adaptive for learning. However, the study by Hofverberg and Winberg (2020a) found no support for such an interaction effect in a Swedish sample. Thus, although our study shows very weak influence of performance goals on Students' achievement when other features of the school environment are also considered, the reasons for this require further attention.…”
Section: Importance Of Motivational Characteristics For Student Achiementioning
confidence: 87%
“…This is in line with the theory of performance effectiveness as a benchmark to state how far the target has been achieved. The greater the goal, the higher the level of effectiveness (Bittner, 2021;Hofverberg & Winberg, 2020;Publika et al, 2020).…”
Section: Discussionmentioning
confidence: 99%